Effects of ZnO nanoparticulate addition on the properties of PMNT ceramics - Promsawat M. (2014)
This research was conducted in order to study the effect of ZnO nanoparticulate addition on the properties of 0.9Pb(Mg 1/3Nb 2/3)O 3-0.1PbTiO 3 [PMNT] ceramics. The PMNT ceramics were prepared by a solid-state reaction. The ZnO nanoparticles were added into PMNT ceramics to form PMNT/xZnO (x = 0, 0.05, 0.1, 0.5, and 1.0 wt.%). The PMNT/xZnO ceramics were investigated in terms of phase, microstructure, and mechanical and electrical properties. It was found that the density and grain size of PMNT ceramics tended to increase with an increasing amount of ZnO content. Moreover, a transgranular fracture was observed for the samples containing ZnO, while pure PMNT ceramics showed only a intergranular fracture. An addition of only 0.05 wt.% of ZnO was also found to enhance the hardness and dielectric and ferroelectric properties of the PMNT ceramics. © 2012 Promsawat et al.